Behavioral syndromes and their effect on dispersal in Notonecta irrorata - Kitchen, Anthony J. (East Carolina University, 2018)
Dispersal is an important life-history characteristic for many organisms, including in the genus of back-swimming insect Notonecta. The propensity to disperse is a behavior that might be affected by an individual's other behavioral tendencies. Correlated behavioral traits, or behavioral syndromes, are evidence for personality in animals and could potentially play a role in dispersal propensity. This research examined whether or not a behavioral syndrome exists in Notonecta irrorata and whether or not these levels of behavior 1) influenced dispersal, 2) were consistent through time, and 3) were consistent when other conspecifics were present. I found that a behavioral syndrome does exist in the foraging behaviors of N. irrorata (swimming time, vegetation use, number of prey consumed, and perching depth). These four traits were correlated along a "boldness gradient" and individuals were sorted into personality types based on where they fell along this bold/passive axis. Bold individuals spent, on average, more time swimming, used vegetation less, consumed more prey items, and perched at shallower depth in the water than passive individuals did. Dispersal propensity was influenced by the type of personality (bold or passive) of an individual. Specifically, passive individuals dispersed from experimental pools more quickly on average than bold individuals, and the dispersal propensity of each personality type was influenced by the personality type of other conspecifics present in the pool. The average levels of each foraging behavior remained consistent through time and were not affected by the presence of another individual, even though the presence of other individuals did affect dispersal behavior in each personality type. This research shows that behavioral consistency is evident in Notonecta and highlights the importance of recognizing animal personality as a legitimate factor in population and meta-population dynamics.
Keywords: Behavioral syndromes; animal personality; Backswimmers (Insects)--Behavior; Backswimmers (Insects)--Dispersal